1967
DOI: 10.1139/v67-439
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of calcium phosphate from solution

Abstract: A method of determining the stoichiometry of metastable phases from nucleation characteristics is described and is applied to calcium phosphate precipitation. The stoichiometric ratio [Ca]/[P] is shown to be 1.49 ± 0.02 in the pH range 7.0–9.1, indicating that it is not hydroxyapatite which normally forms first in the physiological pH region. Characterization of the product by radio isotopes and by infrared spectroscopy and electron diffraction confirms the stoichiometry and indicates that the calcium phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The open probability of these channels increases at low ATP, which fits the finding that P i entry into the SR of skinned muscle fibers is inhibited by ATP (359), although others did not observe this ATP dependency (142,423). Other uncertainties regarding the importance of SR Ca 2ϩ -P i precipitation in fatigue include (423) the concentrations of Ca 2ϩ and P i required to cause precipitation might be higher in the functional SR than in simple salt solutions, Ca 2ϩ -P i may exist in many different forms (456), and unstable complexes dissolve rapidly, which means that more Ca 2ϩ might become available as the [Ca 2ϩ ] SR declines during a tetanic contraction.…”
Section: P I and The Decrease Of Tetanic [Ca 2ϩ ] I In Late Fatiguementioning
confidence: 55%
“…The open probability of these channels increases at low ATP, which fits the finding that P i entry into the SR of skinned muscle fibers is inhibited by ATP (359), although others did not observe this ATP dependency (142,423). Other uncertainties regarding the importance of SR Ca 2ϩ -P i precipitation in fatigue include (423) the concentrations of Ca 2ϩ and P i required to cause precipitation might be higher in the functional SR than in simple salt solutions, Ca 2ϩ -P i may exist in many different forms (456), and unstable complexes dissolve rapidly, which means that more Ca 2ϩ might become available as the [Ca 2ϩ ] SR declines during a tetanic contraction.…”
Section: P I and The Decrease Of Tetanic [Ca 2ϩ ] I In Late Fatiguementioning
confidence: 55%
“…Several authors believed it to be identical in composition to other calcium phosphates, notably brushite (DCPD) (2), octacalcium phosphate (OCP) (3), and tricalcium phosphate (TCP) (6)(7)(8). However, more recent work by Termine and Eanes (9) indicated that the chemical composition of ACP is pH-dependent and that at most short-range order is to be expected.…”
Section: Introductionmentioning
confidence: 99%
“…This ratio has been found in several cases to be 1.45±0.05 which is considerably lower than the value of 1.67 corresponding to HAP which is generally implied as the precipitating mineral. A number of different precursor phases have been postulated to be formed including TCP (Montel et al, 1981;Narasaraju & Phebe, 1996;Walton et al, 1967), OCP (Eanes & Posner, 1968, Posner, 1969 and DCPD (Furedi-Milhofer et al, 1976). On the basis of the analysis of the induction times preceding the spontaneous precipitation of calcium phosphate, it was concluded that at high solution supersaturations the initially forming ACP was converted into an apatitic mineral through an OCP precursor phase formation (Fransis & Webb, 1971).…”
Section: Biomineralization: Physicochemical Backgroundmentioning
confidence: 99%